Sustentabilidade e a gestão compartilhada dos resíduos sólidos no município de Ribeirão Preto/SP: conflitos e desafios - Pirani, Nikolas de Camargo (Universidade Federal de São Carlos, 2010)
In urban Brazil, environmental problems have multiplied and have impacts in the worse conditions of living. The social sciences fall into this debate with the understanding that environmental problems arise as a result of economic and social organization. Are the differences in social form of production that determine what materials to use, the rate that will be used and the interaction with the environment. Currently, the production of solid waste is increasing and its inappropriate disposal in most municipalities. Since the late 1980s, have multiplied the experiences of municipal waste collection programs in partnership with recyclable material, organized in associations and cooperatives. These partnerships are called shared management of municipal solid waste and represent a model that seeks to promote economic, environmental and social. However, in practice, these partnerships face serious challenges to the efficiency of the municipal waste collection. The research aims to examine the guidelines of the joint management of solid waste in the municipality of Ribeirão Preto in order to raise the proposals put into practice and the noticeable results of these policies on an assessment that takes into account the three pillars of sustainability.
Keywords: Resíduos sólidos; Gestão de resíduos sólidos; Lixo urbano; Urban solid waste; Shared management of waste; Urban trash issue; OUTROS::CIENCIAS SOCIAIS